Nursing Care of Acute Pain in Multiple Fractures with Spiritual Therapy Quantum Touch and Finger Holding: A Case Study - Dewi, Risma Eka Putri Arlyani Kusuma; Hakam, Mulia; Sutawardana, Jon Hafan; Shodikin, Mohammad (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
Background: Multiple Fractures or broken bones are a condition where the continuity of the bones is broken in a complex manner, this is caused by trauma caused by frequent traffic accidents. Objective: To analyze the effect of a combination of non-pharmacological therapies Quantum Spiritual Touch Therapy" (QST) and Finger Holding in multiple fraktur patients with acute pain at RSD dr. Soebandi Jember. Method: This research is an observational study with a case study design. Primary data obtained through anamnesis and physical assessment. Assessment of the effect of QST therapy and finger holding was carried out a total period of 35 minutes, 20 minutes for QST therapy and 15 minutes for finger holding therapy, based on initial, process, and final data. Results: The results showed a reduction in pain levels with a Numerical Rating Scale (NRS) was carried out for 6 meetings with the implementation of therapy once a day. Pain levels decreased in the pre-implantation measurements with an average of 5,4 to 4,7 at the time of post-implementation. Discussion: The combination of pharmacological therapy from QST therapy and finger holding aims to help the effectiveness of analgesic drugs by improving the psychological structure with implementations that contain spiritual elements.